Mechanical Performance of a Polyaxial Locking Plate and the Influence of Screw Angulation in a Fracture Gap Model - Kaczmarek, Jakub; Bartkowiak, Tomasz; Schuenemann, Riccarda; Paczos, Piotr; Gapinski, Bartosz; Bogisch, Sandra; Unger, Martin (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to compare the locking compression plate (LCP) with polyaxial locking system (PLS) using single cycle to failure 4-point bending test and to investigate the behaviour of PLS with screws inserted mono- and polyaxially using cyclic fatigue test in two bending directions.Materials and Methods Tests were performed on bone surrogates in a fracture gap model. The 3.5 LCP and 3.5 PLS plates were tested in single cycle to failure. The 3.5 PLS plates with mono- and polyaxial screws were compared in a cyclic fatigue tests in two orthogonal directions. For both experiments, micro-computed tomography (CT) scans were performed pre- and post-testing to investigate the connections between the screw head and the plate hole. Means of forces and cycles needed to failure were statistically compared.Results The PLS plates were on average 30% weaker than LCP plates. Mode of failure was plate bending in the single cycle to failure tests, and plate breakage in the cyclic fatigue tests. Neither screw breakage nor loss of the screw–plate interface occurred. Mono- and polyaxial constructs performed similarly when loaded in the same direction. Micro-CT revealed no additional internal cracks in the plates or screws after testing. It also showed for both PLS and LCP that there was only partial contact of the screw head with the plate hole.Clinical Relevance PLS offers a durable locking system, even when the screws are placed polyaxially. The weaker bending properties of the PLS compared with LCP should be considered during preoperative planning.
Keywords: locking plate; micro-CT; bending; locking screws; polyaxial